Ascertainment of Historic Waters in the US Case Law - E. L. Sokolova (Московский журнал международного права, 2012)
The article examines the application of US Supreme court of international law concerning historic waters; the article focuses on the legal grounds and evidences of the contesting parties that they allege in the US Supreme court to proof the rights to historic waters. The author demonstrate the influence on the decision making of the UN study “Juridical Regime of historic waters, including historic bays” and the Convention on the Territorial Sea and the Contiguous Zone 1958. In addition in the article is given definition of the term “historic waters” that is used in the US case law.